Pengaruh Edukasi Gizi terhadap Kadar Hemoglobin pada Ibu Hamil: Tinjauan Sistematis dan Meta-Analisis - Miranda Zannuba Qotrunnada; Annisa Yumna Fauzi; Trias Mahmudiono (Media Gizi Kesmas, 2025)
Background:  Pregnancy-related anemia is an important women’s health issue with worldwide implications due to its impact on the mother and baby. Nutritional education can increase hemoglobin (Hb) levels through improving women’s knowledge and encouraging more frequent consumption of iron-rich foods and taking folic acid. Despite this, the results that have been produced in previous research are inconsistent. In this regard, the aim of the present systematic review with meta-analysis is to establish whether nutritional counseling is among the best intervention approaches to boost Hb levels and prevent anemia. Objective: To study the effect of nutrition education on hemoglobin levels of pregnant women. Methods: The present systematic review  and meta-analysis adhere to PRISMA 2020 guidelines. A literature review was conducted using the main databases from January 2019 to April 2025. Seven relevant studies were comprised of RCTs and quasi-experimental designs. A statistical analysis using MD of hemoglobin level in the intervention group compared to the control, along with 95% CI was also calculated. The data was analyzed with the aid of a random effect model. Heterogeneity was tested with the aid of the ‘I² statistics and Cochran’s Q test. Sensitivity analysis was also conducted to check the robustness of the pooled data after harassing the study by eliminating each one individually. Results: The meta-analysis included seven studies, including a total of 1,120 pregnant participants. Combined data indicated that the subjects in the nutrition education group had a greater increase in the level of their hemoglobin compared to those in the control group, with a mean difference of 0.73 g/dL (95% CI=0.62–0.84; p<0.00001). There was marked heterogeneity (I²=94%). Additional research demonstrated the efficacy of an integrated approach in this case, counselling bolstered by digital and visual tools over other methods employing only lectures (MD=0.85 g/dL; 95% CI=0.71–0.99). In this case, lectures yielded weaker results (MD=0.52 g/dL; 95% CI=0.41–0.64). Sensitivity analysis verified that the aggregated data were consistent enough that no single study had a disproportionate impact on the overall findings. Conclusion: Nutrition education, with systematic nutrition sessions and practice, has been found to be more effective in improving hemoglobin levels in pregnancy as compared to disorganized education. In light of the continued burden of anemia in pregnancy, the inclusion of systematic and comprehensive nutrition education into antenatal care programs holds the main key to reducing this problem.